TOXICITY AND EFFICACY OF INTRAVITREAL MELPHALAN FOR RETINOBLASTOMA: 25 µg Versus 30 µg. Issue 1 (January 2021) - Liao, Albert; Hsieh, Terry; Francis, Jasmine H.; Lavery, Jessica A.; Mauguen, Audrey; Brodie, Scott E.; Abramson, David H.
Abstract : Purpose: To compare retinal toxicity as measured by electroretinogram, ocular, and patient survival in retinoblastoma treated with intravitreal melphalan at two concentrations (25 vs. 30 µ g). Methods: Single-center, retrospective analysis of retinoblastoma eyes receiving 25- µ g or 30- µ g intravitreal melphalan from September 2012 to January 2019. Ocular toxicity was measured by electroretinogram of evaluable injections in 449 injections in 136 eyes. A repeated-measures linear mixed model with a random intercept and slope was applied to account for repeated measures for each eye. Results: Average decline in electroretinogram after each additional injection was −4.9 µ V (95% confidence interval −6.3 to −3.4); electroretinogram declined by −4.6 µ V (95% confidence interval −7.0 to −2.2) after 25- µ g injections and −5.2 µ V (95% confidence interval −6.6 to −3.8) after 30- µ g injections ( P = 0.66). Injection at a new clock site hour was associated with a −3.91- µ V lower average (95% confidence interval −7.8 to −0.04). Conclusion: Electroretinogram-measured toxicity in retinoblastoma eyes treated with intravitreal injections was not found to be different across 25- µ g and 30- µ g injections. There were no cases of extraocular extension or metastatic deaths in our patient population. Abstract : Supplemental Digital Content is Available in the Text.We did not detect a difference in toxicity as measured by electroretinogram for retinoblastoma eyes treated with 25 µ g versus 30 µ g of intravitreal melphalan. Intravitreal melphalan injections at new sites on the eye were associated with increased electroretinogram-measured toxicity.